2021
DOI: 10.1096/fj.202002111rr
|View full text |Cite
|
Sign up to set email alerts
|

The CR9 element is a novel mechanical load‐responsive enhancer that regulates natriuretic peptide genes expression

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…Cardiomyocytes secrete NPs into the systemic circulation in response to myocardial mechanical loading 2 ; thus, the elevation of plasma NP is essential to cardiac hypertrophy or failure 1 . Previous studies have shown that plasma BNP levels are well correlated with LVMI, that is, LV hypertrophy and LV diastolic function 27,28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiomyocytes secrete NPs into the systemic circulation in response to myocardial mechanical loading 2 ; thus, the elevation of plasma NP is essential to cardiac hypertrophy or failure 1 . Previous studies have shown that plasma BNP levels are well correlated with LVMI, that is, LV hypertrophy and LV diastolic function 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Both atrial natriuretic peptide (ANP) and B‐type natriuretic peptide (BNP), encoded by Nppa and Nppb genes, respectively, are synthesized predominantly in the cardiac myocytes and released into the systemic circulation in response to myocardial wall stretching. 1 , 2 Natriuretic peptides (NPs) exert pleiotropic effects, such as the excretion of both electrolytes and water from the kidneys, reducing vascular tone, and demonstrating anti‐hypertrophic and anti‐fibrotic effects in the heart. 1 Indeed, genetic variation in or near Nppa , Nppb , and Npra genes encoding natriuretic peptide receptor A (NPRA) are associated with regulation of either blood pressure or cardiac hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“… 24 We previously identified the DNA regulatory element, putative enhancer CR9, for Nppa and Nppb , which responds to mechanical loads by upregulating Nppa and Nppb expression in cardiomyocytes. 2 Mice with a deletion of the regulatory DNA region, including the CR9 element, show an endocrine deficiency in ANP and BNP. 7 Accordingly, unknown variants within the regulatory DNA regions may lead to endocrine deficiencies in NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the plasma natriuretic peptide (NP) levels are clinically valuable biomarkers for assessing the presence and severity of cardiac hemodynamic stress. 1 , 2 Elevated LVFP is one of the most important factors that trigger not only LV hypertrophy (LVH) but also the transcriptional activation of NPs. A positive correlation between high plasma BNP levels, LVH, and diastolic dysfunction has been demonstrated in patients with heart failure (HF) or hypertension.…”
mentioning
confidence: 99%